CONJUCTURE EFFECT OF OPERATIONAL COST FOR INCREASING FINANCIAL PERFORMANCE PT. GOTONG ROYONG JAYA - Sinta, Irada; Tambarta Kembaren, Emmia; F, Fadli (CV. Radja Publika, 2021)
This study aims to determine how the Effect of Operational Costs on the Financial Performance of PT. Gotong Royong Jaya. The research method used is quantitative data method. While the data used is secondary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of the variable Operating Costs on Financial Performance by using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using simple regression analysis and t-test indicate that: the t-table value of the Operating Cost variable is 6.862 > the t-table value (df: : 35%) is 2. 030 so it can be concluded that the Operational Cost has a positive and significant effect on the Financial Performance of PT. Gotong Royong Jaya.